Hypertensive toxemia of pregnancy (current state of its pathogenesis) - Pérez, Manuel (2015)
Despite the years and although in recent times the study of hypertensive toxemia was more promising paths appear to have directed, you can still repeat that its pathogenesis continues to justify the name to be given to "disease of theories' (Zweifel). But before tackling the list of currently more grip it is given as determinants of eclampsismo and eclampsia, it must refer a number of facts of predisposing factors as to "facilitate" its outbreak.